Association between allergic rhinitis-related factors and sleep duration in adolescents: Korea National Health and Nutrition Examination Survey V (2010–2012). (March 2021) - Lee, Kijeong; Choi, In Hak; Hong, Yeji; Lee, Hoyoung; Lee, Sang Hag; Kim, Tae Hoon
Abstract: Objectives: Previous studies have shown that sleep and allergic rhinitis (AR) is closely associated, bidirectionally affecting each other. Adolescence is a period that adequate sleep is essential, and the burden of AR increases, both of which greatly affect the quality of life. The aim of the present study was to investigate the correlation between inappropriate sleep duration and each AR-related subjective/objective factor in Korean adolescents. Methods: We analyzed the data of 1936 adolescents aged between 12 and 18 years who participated in the Korea National Health and Nutrition Examination Survey from 2010 to 2012. Data on sleep duration, physician-diagnosed AR, and presence of rhinitis symptoms were collected using a self-administered questionnaire. Nasal endoscopic findings, including watery rhinorrhea and pale inferior turbinate mucosa, and aeroallergen sensitization based on serum specific immunoglobulin E levels were examined. Results: There was a higher prevalence of AR (23.68%) in the inappropriate sleep duration group than in the control group (16.56%; odds ratio = 1.56, p = 0.0024). The presence of endoscopic findings of AR showed a positive association with inappropriate sleep duration in males (odds ratio = 1.52, p = 0.008). In addition, in all three indoor allergens investigated, aeroallergen sensitization was not associated with inappropriate sleep duration. Conclusion: Inappropriate sleep duration was associated with increased prevalence of AR in Korean adolescents. Especially, this association was relevant in nasal endoscopic findings in male.